Medial temporal lobe functional connectivity predicts stimulation-induced theta power. Issue 1 (December 2018) - Solomon, E.; Kragel, J.; Gross, R.; Lega, B.; Sperling, M.; Worrell, G.; Sheth, S.; Zaghloul, K.; Jobst, B.; Stein, J.; Das, S.; Gorniak, R.; et al.
Abstract Focal electrical stimulation of the brain incites a cascade of neural activity that propagates from the stimulated region to both nearby and remote areas, offering the potential to control the activity of brain networks. Understanding how exogenous electrical signals perturb such networks in humans is key to its clinical translation. To investigate this, we applied electrical stimulation to subregions of the medial temporal lobe in 26 neurosurgical patients fitted with indwelling electrodes. Networks of low-frequency (5–13 Hz) spectral coherence predicted stimulation-evoked increases in theta (5–8 Hz) power, particularly when stimulation was applied in or adjacent to white matter. Stimulation tended to decrease power in the high-frequency broadband (HFB; 50–200 Hz) range, and these modulations were correlated with HFB-based networks in a subset of subjects. Our results demonstrate that functional connectivity is predictive of causal changes in the brain, capturing evoked activity across brain regions and frequency bands. Direct electrical brain stimulation can induce widespread changes in neural activity, offering a means to modulate network-wide activity and treat disease. Here, the authors show that the low-frequency functional connectivity profile of a stimulation target predicts where induced theta activity occurs.